Analysis of Foreign Direct Investment and Economic Growth in Nigeria: Application of Spatial Econometrics and Fully Modified Ordinary Least Square (FMOLS). Issue 3 (August 2019) - Olofin, Olabode Philip; Aiyegbusi, Oluwole Oladipo; Adebayo, Abayomi Ayinla
Based on the controversy surrounding the determinants of foreign direct investment (FDI) inflow from one country to another and the suggestion that inflow of FDI might be a result of countries' locations, this study therefore revisits the determinants of FDI and economic growth by testing for the roles of country's location in the determination of the inflow of FDI to Nigeria. Unlike other studies, this study finds that countries' locations do not play any significant role in determining FDI inflow to Nigeria. The study, therefore, employs fully modified ordinary least square (FMOLS) to examine the determinants of FDI in Nigeria. The FMOLS results show that FDI, manufacturing sector, tax revenue, financial development, health expenditure, net trade and human capital have a positive relationship with income growth. These results were statistically significant except for tax revenue, net trade and human capital. These results support the argument that these variables are important determinants of economic growth. The article also finds a negative and statistically significant relationship among FDI, income growth, import and capital formation. These results are in conformity with economic theory in the sense that import of goods and services constitutes a leakage in the economy. Negative impact of capital formation and security could be associated with the prevailing high level of corruption, sharing of security votes and misappropriation of funds among the public officials in Nigeria. JEL Codes: F23, F26, F21, H24